Implementation research to develop and optimize delivery models for evidence-based anemia control interventions in India: Protocol for the precision-driven response for anemia control and sustainable health (PRAKASH) study - Priyanka Gupta Bansal; Sarmila Mazumder; Neeraj Sharma; Ragini Kulkarni; Prashanth Thankachan; Pankaj Prasad; Bhuputra Panda; Santosh Kumar Banjara; Bharati Kulkarni; Ranadip Chowdhury; Ketaki Chandiok (PLoS ONE, 2026)
Background Government of India launched Anemia Mukt Bharat (AMB) program in 2018. Despite its implementation, the prevalence of anemia remains high. To address the gaps in coverage, adherence and effective implementation, the Indian Council of Medical Research (ICMR) initiated the Pr ecision driven R esponse for A nemia C ontrol a nd S ustainable H ealth (PRAKASH) study. It is an implementation research study aimed at co-developing and optimizing a district-level model of evidence-based anemia control interventions. The intended goal is to reduce anemia prevalence to 20% or lower through scalable, context-specific, and sustainable strategies. Methods This multi-site study targets six key population groups: children (aged 6–59 months and 5–9 years), adolescents boys and girls (10–19 years), women of reproductive age (20–49 years) and pregnant women. Interventions are anchored in six pillar i. Test–Treat-Track until resolution, ii. prophylactic iron and folic acid supplementation, ensuring high complianceiii. anemia-relevant health interventions, iv. fortified rice distribution, v. dietary diversification and promotion of iron-rich foods, and vi. behavior change communication through Jan Andolan. Anemia prevalence will be estimated through a series of community-based cross-sectional surveys. Mixed methods approach will be employed to assess barriers and enablers at the individual, household, facility, and community levels. The study will utilize implementation science frameworks, including Consolidated Framework for Implementation Research (CFIR) and Expert Recommendations for Implementing Change (ERIC), to guide iterative implementation, real-time model refinement, and monitoring of performance. Information on outcome indicators will be collected to evaluate anemia prevalence, fidelity, feasibility, and service delivery improvements. Conclusion The study will try to readdress the implementation challenges across diverse regions and aims to develop a comprehensive and replicable model for the AMB 2.0 program. The study is likely to contribute to the global evidence base on implementation science for anemia reduction in low- and middle-income countries.